2022
DOI: 10.1177/10731911221118673
|View full text |Cite
|
Sign up to set email alerts
|

Networks of Neuropsychological Functions in the Clinical Evaluation of Adult ADHD

Abstract: This study applied network analysis to explore the relations between neuropsychological functions of individuals in the clinical evaluation of attention-deficit/hyperactivity disorder (ADHD) in adulthood. A total of 319 participants from an outpatient referral context, that is, 173 individuals with ADHD (ADHD group) and 146 individuals without ADHD (n-ADHD group), took part in this study and completed a comprehensive neuropsychological assessment. A denser network with stronger global connectivity was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 139 publications
(193 reference statements)
2
13
0
Order By: Relevance
“…At the evaluation, ADHD patients showed psychiatric comorbidities (see Table 1), but no information was provided about the diagnostic criteria or the ADHD treatment status. In line with this, 1 year later and on an independent sample with similar features (comorbidities/treatment), the same authors found no difference in neurocognitive measures between the study groups, except for the number of omissions in the vigilance test (Guo et al, 2022).…”
Section: Neuropsychological Assessment Using Multiple Objective Measuressupporting
confidence: 52%
See 1 more Smart Citation
“…At the evaluation, ADHD patients showed psychiatric comorbidities (see Table 1), but no information was provided about the diagnostic criteria or the ADHD treatment status. In line with this, 1 year later and on an independent sample with similar features (comorbidities/treatment), the same authors found no difference in neurocognitive measures between the study groups, except for the number of omissions in the vigilance test (Guo et al, 2022).…”
Section: Neuropsychological Assessment Using Multiple Objective Measuressupporting
confidence: 52%
“…First of all, ADHD patients had comorbid psychiatric disorders in almost all of the studies examined (Edebol et al, 2012;Fasmer et al, 2016;Guo et al, 2021Guo et al, , 2022Holst & Thorell, 2013;Marshall et al, 2016;Pettersson et al, 2018;Söderström et al, 2014). These may have affected the cognitive performance of the patients, making it difficult to isolate the contribution of other conditions from the effect of ADHD itself.…”
Section: Discussionmentioning
confidence: 99%
“…Larger samples would yield more robust findings and may allow the investigation of moderating factors, such as symptom presentation, comorbidities, or medication status. Support for the robustness of our results is given by the good psychometric properties of our instruments and a similar distribution of scores in one-time assessments on independent and large clinical samples [ 32 , 33 ]. Second, some of the participants (7 of 21) were additionally diagnosed with one or more comorbid psychiatric disorders other than ADHD, which may confound our findings.…”
Section: Limitations and Future Directionsmentioning
confidence: 63%
“…Thus, deficits in attention are significantly associated with and may result in deficits in complex cognitive functions. Further, a network study of cognitive functions on a large sample of adults with ADHD demonstrated that selective attention and vigilance have a central role and high expected influence on other cognitive functions, underscoring the strong interrelation between attention and various other cognitive functions [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include genetic and environmental factors like smoking during pregnancy, stress, infection, poverty, trauma, and exposure to toxicants [ 15 , 16 , 17 , 18 , 19 , 20 ] that can lead to changes in brain structure, catecholaminergic neurotransmission, and to specific symptoms like inhibitory and attentional deficits [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Recent studies have demonstrated that ADHD is associated with various cognitive dysfunctions and structural changes [ 6 , 28 , 29 , 30 , 31 ]. A study on the neuropsychological domains showed that patients with ADHD had deficits in sustained attention, working memory, variability of reaction times, and delay aversion [ 32 ].…”
Section: Introductionmentioning
confidence: 99%